The Heterogeneous Impact of Financial Development on Green Total Factor Productivity - Li, Tinghui; Liao, Gaoke (Frontiers in Energy Research, 2020)
This study examines the heterogeneity impact financial development on green total factor productivity for 40 countries, over the period 1991 to 2014. Specifically, this paper describes financial development from the three aspects of banking, securities and insurance. In developing countries, the inverted U-shaped relationship exists between financial development and green total factor productivity, whether it is in bank development, securities development or insurance development. In developed countries, the development of bank and insurance tends to adversely affect green total factor productivity, while the development of securities has always had a positive impact on green total factor productivity. Securities development is more conducive to improving green total factor productivity than bank development.